Men Have Gender and Women Are People: A Structural Approach to Gender and Violence - Applin, Samantha (Violence against women, 2023)
The relationship between violence and patriarchal gender systems is structural and coconstitutive; yet structural analyses that account for gender in explanations and conceptualizations of violence are often absent from violence scholarship. Additionally, there are numerous underassessed areas in more gender-nuanced, “gender-based” violence paradigms. We address the shortcomings of both types of research and propose a cohesive theoretical framework that captures the ways in which violence is patriarchy-enhancing and patriarchy-facilitated. Violence shapes and influences gender performances and structures and, concomitantly, the gender order shapes and influences violence in given contexts.